Coaching across cultures new tools for leveraging national, corporate, and professional differences - Rosinski, Philippe (London Nicholas Brealey Pub, 2003)
Whether working in another country or bridging corporate and professional boundaries, the demands of global business require new ways of managing and motivating people. Author Philippe Rosinski introduces an innovative form of coaching to meet the demands of today's diverse and international workplace: Coaching Across Cultures: New Toold for Leveraging National, Corporate and Professional Differences. While the concept of culture generally evokes nations- as in Spanish or French culture- Coaching Across Cultures addresses cultural differences from many perspectives: national, corporate or professional. These cultural components have a significant impact on every one of our interactions: how we think, organize ourselves, define our purpose, relate to power, view time and cope with uncertainty. With plenty of real life examples and activities, Rosinski offers new approaches to practical and effective coaching methods to help you push beyond the confines of your own culture's norms when working with clients or coaching a team. Written for coaches, executives, and managers, Coaching Across Cultures demonstrates how one can discover creative solutions to problems and leverage cultural differences, turning powerful ideas into action to facilitate the highest performance possible.
Includes bibliographical references ([281]-304)
Keywords: Corporate culture